Influence of pitfall designs and use of baits on the capture of small mammals in Southern Minas Gerais, Brazil - doi: 10.4025/actascibiolsci.v35i4.17498 (Acta Scientiarum. Biological Sciences, 2013)
Each kind of trap tends to be selective on species sampled, in a way that each one only reveals part of the abundance and species richness of the community sampled. In this way, in order to know the factors that affect the success of sampling methods is crucial for a better planning of experiments and data analysis. The aim of this study was to evaluate the factors that affect the success of pitfall traps in capturing small mammals, such as trap size, designs and use of bait. The study was carried out in two reserves inside the campus of the Universidade Federal de Lavras (UFLA), in South Minas Gerais State, Brazil. In total, 65 specimens belonging to 8 species were caught. Different types of trap design (Y-shaped and I-shaped) have not influenced the capture success of pitfalls. The same result was obtained for the different size of buckets, in exception for Oligoryzomys flavescens, in which larger buckets were more efficient. The use of baits was considered not necessary.